Changing What We Might Have Done on Our Own: Improving Classroom Culture and Learning through Teacher Collaboration - Randall, Régine; Marangell, Joseph (The Clearing House: A Journal of Educational Strategies, Issues and Ideas, 2020)
Student achievement is not always the equivalent of what students learn, especially when educators use their feedback to shape daily instruction. When students share their classroom experiences, we can determine better ways to create interdisciplinary partnerships, manage workload, enhance historical understandings, and communicate conclusions. Being able to trust in what students are doing in class, how well they are doing it, and what they will be able to do motivated the authors, who are two veteran educators, to reevaluate when their own teaching seemed most effective. What they discovered is incongruent with the traditional delivery of instruction by a single teacher. The authors found that their collaboration as co-teachers not only benefited their students but increased their own professional learning in terms of pedagogy, content knowledge, and the use of disciplinary literacy.
_eprint: https://doi.org/10.1080/00098655.2020.1828240
Keywords: Co-teaching; dept.cur; interdisciplinary partnerships; peer-reviewed; professional collaboration; secondary education; student engagement

One Story Creates Another: Using Book Clubs to Promote Inquiry in the Content Areas - Randall, Regine E.; Marangell, Joseph P. (ie: inquiry in education, 2020)
Keywords: dept.cur; peer-reviewed; ⛔ No DOI found